The Italian Version of the Cognitive Style Indicator and its Association with Decision-Making Preferences. Issue 1 (2nd January 2018) - Miceli, Silvana; de Palo, Valeria; Monacis, Lucia; Cardaci, Maurizio; Sinatra, Maria
Abstract : The Cognitive Style Indicator (CoSI) includes 3 cognitive dimensions: creating (flexible, open-ended and inventive), knowing (emphasizing facts, details, objectivity, and rationality), and planning (guided by preferences for certainty and well-structured information). The first aim of this research was to validate the 3-factor structure of the CoSI within the Italian context. The second was to verify whether cognitive styles, as measured by the CoSI, accounted for individual differences in decision-making processes. Two studies were conducted using 2 different samples ( n  = 549 and n  = 397). Confirmatory and multigroup factor analysis corroborated the 3-factor model and the measurement invariance of the instrument across genders. Reliability indices showed good internal consistency, as well as good levels of convergent and discriminant construct validity. Results from structural equation model revealed that cognitive styles, as measured by the CoSI, predicted individual differences in intuitive and deliberative decision-making processes. Findings gave evidence for the validity of the Italian version of the CoSI and for the causal relationship between cognitive styles and decision-making processes. Further research is needed to explore a more comprehensive model that includes, for example, personality.